Magnetic-field-induced phase transitions in the quasi-one-dimensional organic conductor HMTSF–TCNQ - Murata, K.; Fukumoto, Y.; Yokogawa, K.; Takaoka, R.; Kang, W.; Brooks, J.S.; Graf, D.; Yoshino, H.; Sasak, T.; Kato, R. (Физика низких температур, 2014)
Motivated by an interest to see if the field-induced (FI) phase in the charge-density wave (CDW) system is
similar to the field-induced-SDW (FISDW) in (TMTSF)₂X, (TMTSF: tetramethyltetraselenafulvalene), we examined
the magnetic-field-induced phases in a quasi-one-dimensional (Q1D) organic conductor HMTSF–TCNQ
(hexamethylene-tetraselenafulvalene-tetracyanoquinodimethane) under a pressure of 1.1 GPa, where the CDW
occurring at 30 K is suppressed. The work was carried out by measurements of angular-dependent
magnetoresistance oscillations and exploratory work on the Hall effect. It turned out that the FI-phase, most likely
a FICDW for B > 0.1 T, accompany a quantum Hall effect, and the FI-phase transitions are controlled by the
field component along the least conducting axis. Above 10 T, the lowest Landau level of the small 2D Fermi
pocket (due to incomplete nesting of Fermi surface) exceeds the Fermi level, reaching the quantum limit. Although
there are many differences between the CDW (HMTSF–TCNQ) and SDW ((TMTSF)₂X) systems, a similar
scenario for field-induced phases seems to hold.